PELAKSANAAN PERJANJIAN PENITIPAN HEWAN DI RUMAH SAKIT HEWAN PROF. SOEPARWI - , AUDY FERDIANANDA, R.A. Antari Innaka T., S.H., M.Hum ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The animal care agreement is one of an important part when someone wants to have their pet being taken care of in the Veterinary Hospital. It is important to know if there is such an agreement or not because the terms and conditions about the implementation of the animal care agreement are regulated on that agreement. It also contains the right and obligation that have to be fulfilled by both parties. The purpose of this research is to know the implementation of the animal care agreement specifically in Prof. Soeparwi Veterinary Hospital, Sleman, D.I. Yogyakarta. The methods of this research is non-purposive sampling which means the author decides who the respondents are. In this research, author found the fact that there are some breaches of contract that have occured between both Veterinary Hospital and the owner of the pet. The writter also found the solution to problems that occur between those parties relating to the agreement.